QUERCETIN-INDUCED MYOCARDIUM MORPHOLOGICAL LESIONS IN EXPERIMENTAL DIABETES MELLITUS TYPE 1 - Posokhova, K.A.; Stechyshyn, I.P. (World of Medicine and Biology, 2015)
The effect of water-soluble and liposomal quercetine forms on the morphological changes in the myocardium under type 1 diabetes was experimentally studied on rats. The animals were selected on the basis of previous blood glucose level determination. Type 1 diabetes correction by corvitine was found to decrease the vascular wall permeability that was histologically confirmed by the changes of its thickness. Besides, it was shown to decrease both the damage to the endothelial layer and erythrocytes aggregation in the vascular lumen, thus contributing in part to the improvement of the cellular sarcoplasm structural state. Lipoflavon was found to reduce the damage mainly to arterial bloodstream whereas structural changes in the cardiac hystiocytes would not occur. However, moderate perivascular and stroma oedema were observed.
Keywords: diabetes mellitus; morphology; hart; quercetin